Some peculiarities in ontogeny of Homo sapiens comparing with mammalian and Primates growth - Kozieł, Sławomir; Siniarska, Anna (Studia Ecologiae et Bioethicae, 2004)
During ontogeny, there are many phenomena that significantly differentiate humans from other mammals, including Primates. The present considerations and analysis of regression applied for many species to illustrate allometric relations of developmental spurts of height and weight to final values of these parameters in adults, allow to compare processes of growth of Homo sapiens with other Primates and to submit the following results: In Homo sapiens, the maximal rate of growth in length and body mass exists at the prenatal period (during gestation), and after birth, it decelerates. In the evolution of human ontogeny, two new stages occurred: The first one is „childhood" which is manifested by slow body growth and intense brain development. The second one is named „adolescence" and includes pubertal spurt of many body variables. In Humans, as compare with other Primates, the infancy and juvenile stages had been shortened. Human puberty begins when the postnatal rate of growth in height and weight is the lowest since birth and there is a considerable delay in puberty and sexual maturation than in other Primates. The adolescent growth spurt shortens the time needed to reach sexual maturity, which could have been much longer as the result of a slow growth that childhood. Sexual dimorphism in the intensity of pubertal spurt of body mass is smaller in Humans than in other Primates. On the contrary, sexual dimorphism in the onset of puberty and growth rate in height at this stage is rather well manifested. The adolescent stage is divided into two parts because there is a delay of years between puberty and the onset of the adult reproductive stage of life.